DIGITAL DEVOTION AND ECONOMIC PRACTICES: HOW BTS ARMY NAVIGATES CAPITALISM IN THE ATTENTION ECONOMY - Fitrianatsany, Fitrianatsany; Himmati, Risdiana; Meirini, Dianita; Yustivira, Helena (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study explores the digital consumption practices of the global BTS ARMY fandom within the framework of the attention economy and postmodern cultural theory. Drawing on a qualitative case study of ARMY communities in Indonesia, the research investigates how fans collectively organize streaming, voting, and merchandise purchasing through digital platforms. These activities are not merely economic transactions but serve as socially meaningful practices that construct symbolic identity and community solidarity. Utilizing theoretical frameworks from Goldhaber’s attention economy, Baudrillard’s simulacra and hyperreality, Bourdieu’s cultural and symbolic capital, and Jenkins’ participatory culture, the study demonstrates that fandom products function as hyperreal symbols that mediate social relations and reproduce status hierarchies within the fan community. The findings show that ARMY operates as an active agent in the digital cultural economy, converting attention and symbolic participation into real economic and social value. This research contributes to economic sociology and digital cultural studies by highlighting how transnational fandom operates as a strategic and organized force within the global digital marketplace, reshaping conventional understandings of cultural consumption and identity.